Pengaruh Metode Pembelajaran Terhadap Hasil Belajar IPA SMP Ditinjau dari Kecerdasan Intrapersonal Peserta Didik - Risky Sarapung; Julia Ismail; Risky Richlos Sarapung (Peneliti.net, 2021)
This study aims to determine the effect of learning methods and students' intrapersonal intelligence on science learning outcomes. This study uses a quantitative experimental research method with a research design using ANOVA Two Paths with Treatment by level 2 × 2. The population in this study was class IX students of SMP N 9 Morotai Island with a sample of 16 students in class IX-1 and class IX-2 students, totaling 16 people. The results of this study indicate (1) there are significant differences in science learning outcomes between students who are taught using experimental learning methods and students who are taught using demonstration learning methods (2) there is an interaction between the use of learning methods and intrapersonal intelligence on science learning outcomes (3 ) there is a significant difference in science learning outcomes between students who are taught using the Experimental learning method with an average score of 91.71 and students who are taught using the demonstration learning method with an average score of 78.39 especially for students who have high intrapersonal intelligence. (4) there is a significant difference in science learning outcomes between students who are taught using the Experimental learning method with an average score of 85.30 and students who are taught using the demonstration learning method with an average value of 73.84 specifically for students who have intelligence.low intrapersonal.